Види інформаційних загроз у системах електронного документообігу - Чередник, Людмила (Видавництво Львівської політехніки, 2019)
The theses address the issue of the types of information threats in the electronic document management system, presents a general classification of information security threats.
Keywords: information system; information threat; cyber attack; virus; information security